The Effect Of Brand Image, Product Quality, Service Quality And Promotion On Skintific Skincare Purchase Decisions In Semarang City - Rizkiyatul, Sinta; Prabowo, Heri; Sijabat, Rauly (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of brand image, product quality, service quality, and promotion on the purchasing decision of Skintific skincare products in Semarang city. The sampling technique used in this study was purposive sampling, employing the Lemeshow formula with a total of 96 respondents by distributing questionnaires. The data analysis technique uses Smart PLS 23. The results of the study indicate that (1) Brand image does not affect purchasing decisions, (2) Service quality does not affect purchasing decisions, (3) Product quality affects purchasing decisions, and (4 ) Promotion affects purchasing decisions. The coefficient of determination in this study is 77%, which means that brand image, product quality, service quality, and promotion influence the purchasing decision variable by 77%. The remaining 23% is influenced by other variables not included in this study.